2011
DOI: 10.3113/fai.2011.1081
|View full text |Cite
|
Sign up to set email alerts
|

Plantar versus Dorsomedial Locked Plating for Lapidus Arthrodesis: A Biomechanical Comparison

Abstract: Plantar plating appears to offer biomechanical benefit. Clinical studies will be required to show whether this translates into earlier resumption of weightbearing and into lower rates of nonunion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
56
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 18 publications
8
56
1
Order By: Relevance
“…In contrast, the results of the present study reveal no statistically significant correlation between BMD and biomechanical stability of variable locking plate fixation. These findings correspond to findings of other studies investigating plate fixation [29,32,35]. In conclusion, based on the results of the present study we consider variable locking plate fixation superior to single screw fixation concerning biomechanical stability for proximal chevron osteotomy.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…In contrast, the results of the present study reveal no statistically significant correlation between BMD and biomechanical stability of variable locking plate fixation. These findings correspond to findings of other studies investigating plate fixation [29,32,35]. In conclusion, based on the results of the present study we consider variable locking plate fixation superior to single screw fixation concerning biomechanical stability for proximal chevron osteotomy.…”
Section: Discussionsupporting
confidence: 79%
“…Some of them found correlations [20,29,32,35] whereas others were not able to identify a significant relationship between BMD and fixation method [34]. In the present study, we found significant negative correlation between BMD and the maximum tolerated load until construct failure occurred.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Promising results could be achieved with the use of the plantar plate for TMT I arthrodesis [12,16]. In a biomechanical study Marks et al described a clear advantage of the plantar osteosynthesis with a one-third tubular plate over a screw osteosynthesis in neuropathic feet [11].…”
Section: Discussionmentioning
confidence: 97%